الصكوك الإسلامية وأثرها على ربحية المصارف الإسلامية دراسة حالة مصرف الراجحي خلال الفترة ) 2008 - 2021 ): Islamic Sukuk And Their Impact On The Profitability Of Islamic Banks A Case Study Of AL_Rajihi Bank During The Periode ( 2021 - 200 - عبد القادر طاري,; حمزة مقاتل, (Journal of North African Economies, 2025)
This study aims to identify the impact of investing in sukuk on the profitability of Islamic banks, As one of the financial tools and investment channels for Islamic financial institutions, Through a case study, the profitability of Al-Rajhi Bank in the Kingdom of Saudi Arabia was affected by its investment in Islamic sukuk during the period 2008-2021, In order to complete the study, the standard method was adopted using the VAR autoregressive beam model , Using the Eviews 12 program based on data obtained from the annual reports of Al Rajhi Bank, The study reached a number of results, including: There is a direct relationship between the volume of profits achieved in Al-Rajhi Bank and the volume of Islamic sukuk, This means that the higher the volume of sukuk invested in by Al Rajhi Bank in a year, the higher the value of profits achieved in the following year, and vice versa in the case of a decrease, The study also concluded that the investment of Islamic banks in sukuk has strong positive effects on the size of their future profits.